Altered CD4+ T cell immunity in nurses occupationally exposed to viral pathogens. (19th September 2018) - Elias, G; Souquette, A; Heynderickx, S; De Meester, I; Jansens, H; Beutels, P; Van Damme, P; Smits, E; Thomas, P G; Van Tendeloo, V; Ogunjimi, B
Summary: Pathogen exposure, including but not limited to herpesviruses, moulds the shape of the immune system, both at a basal state and in response to immune challenge. However, little is known about the impact of high exposure to other viruses on baseline immune signatures and how the immune system copes with repetitive exposures to maintain a balanced functionality. Here we investigated baseline immune signatures, including detailed T cell phenotyping, antigen-specific CD4 + and CD8 + T cell responses and cytokine profile in paediatric (PED) nurses, who have high occupational exposure to viral pathogens including varicella zoster virus (VZV) and respiratory viruses, and in neonatal intensive care unit (NICU) nurses, as a control group with infrequent occupational exposure. Our results show a lower CD4 + T cell response to two VZV proteins (IE62 and gE) and to tetanus toxoid (TT) in PED nurses who are cytomegalovirus (CMV)-seronegative, compared to CMV-seronegative NICU nurses, and that the decline might be more pronounced the more sustained the exposure. This decline might be due to an attrition of VZV- and TT-specific T cells as a result of the continuous pressure on the CD4 + T cell compartment. Moreover, our data suggest that the distinct T cell phenotypes known to be associated with CMV-seropositivity might be less prominent in PED nurses compared to NICU nurses, implying a plausible attenuating effect of occupational exposure on CMV-associated immunosenescence. Overall, this pilot study reveals an impact of occupational exposure to viral pathogens on CD4 + T cell immunity and supports further investigation in a larger cohort. Graphical Abstract: